Kingella kingae cytotoxin RtxA induces an innate immune response in oral epithelial cells - Eliska Ruzickova; Karyna Zhuk; Kevin Munoz Navarrete; Adriana Osickova; Radim Osicka (Current Research in Microbial Sciences)
The genus Kingella comprises four common species: the commensals K. oralis and K. denitrificans, the emerging paediatric pathogen K. kingae and the novel species K. negevensis. Improved diagnostic methods have led to the recognition of K. kingae as a major cause of septic arthritis in young children. The key virulence factor responsible for the pathogenesis of K. kingae is its cytotoxin RtxA, which is thought to facilitate host invasion. After binding to target cells, RtxA inserts into the host cell membrane and forms ion-conducting membrane pores that disrupt normal cell physiology and ultimately lead to cell death. In this study, we analysed the pro-inflammatory response of oral epithelial cells to a clinical isolate of K. kingae, its isogenic RtxA-deficient mutant and the commensals K. oralis and K. denitrificans, which do not produce RtxA. The results show that infection of cells with K. kingae, but not with the RtxA-deficient mutant and the commensal species, leads to increased expression and secretion of certain pro-inflammatory cytokines and chemokines. Furthermore, the RtxA-producing K. kingae, but not the RtxA-deficient mutant, upregulated the expression of DEFB4A and SLPI genes encoding antimicrobial peptides. These findings demonstrate that the RtxA toxin induces an innate immune response in oral epithelial cells.